2019
DOI: 10.18203/2320-6012.ijrms20191295
|View full text |Cite
|
Sign up to set email alerts
|

Study of asymptomatic bacteriuria in pregnant women: prevalence, isolates and their antibiotic sensitivity pattern

Abstract: Background: Asymptomatic bacteriuria (ASB) is common in pregnant women due to morphological and physiological changes in the genitor-urinary tract, which untreated may lead to complications like pyelonephritis and may also effect the fetus. The objective of our study was to determine the prevalence of ASB in pregnant women, to identify the organisms responsible and their antibiotic sensitivity pattern.Methods: A clean catch midstream urine was collected from 250 pregnant women in different trimesters attending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…Regarding the antimicrobial susceptibility pattern of the bacteriuria, we found that the isolated organisms highly susceptible to Imipenem were considered the most effective antibiotics against the most common organisms causing asymptomatic bacteriuria in this study, which were in agreement with other studies in India by Prasanna et al, 2015;and Sandhya et al, 2019, followed by meropenem, amoxyclav, ceftriaxone and ciprofloxacin, however E. coli isolates and other isolates were shown high level of resistant to Penicillin G, erythromycin, clindamycin and cotrimaxazole, respectively. This was found in agreement with other studies by Arredondo-García and Amábile-Cuevas, 2008; Ayoyi et al, 2017;Gohar et al, 2019;Emami et al, 2020. However the antibiotic susceptibility patterns against UTI are shown to be different in different geographical locations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding the antimicrobial susceptibility pattern of the bacteriuria, we found that the isolated organisms highly susceptible to Imipenem were considered the most effective antibiotics against the most common organisms causing asymptomatic bacteriuria in this study, which were in agreement with other studies in India by Prasanna et al, 2015;and Sandhya et al, 2019, followed by meropenem, amoxyclav, ceftriaxone and ciprofloxacin, however E. coli isolates and other isolates were shown high level of resistant to Penicillin G, erythromycin, clindamycin and cotrimaxazole, respectively. This was found in agreement with other studies by Arredondo-García and Amábile-Cuevas, 2008; Ayoyi et al, 2017;Gohar et al, 2019;Emami et al, 2020. However the antibiotic susceptibility patterns against UTI are shown to be different in different geographical locations.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, females are more susceptible to UTIs because of the short length of the urethra along with close anal canal. Pregnant women are more commonly affected than normal women due to some anatomical changes occurring during pregnancy (Sandhya et al, 2019). The association of ASB with adverse outcomes of pregnancy is a matter of concern of infections risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respecto al tipo de infección urinaria más frecuente en los resultados del presente estudio, la prevalencia de bacteriuria asintomática es del 7,69%, resultado cercano al 8,7% encontrado en Dharan (Nepal) por Thakur y col., 31 ; aunque levemente mayor al 6,1% descrito por Ahmad y col., 32 en un grupo de 392 embarazadas en Srinagar, Kashmir (India); no obstante, en un reciente estudio publicado por Sandhya y col. 33 en el mismo país, se encontró una prevalencia ligeramente mayor (9,2%) en 250 gestantes. Con relación a la cistitis aguda, los hallazgos de este estudio, difieren del 1,3% reportado por Harris y col., 7 en el Centro médico Wilford Hall, San Antonio, Texas (EEUU), en una muestra de 9734 mujeres; así como al 54% descrito por Sanín-Ramírez y col., 34 en Medellín (Colombia), diferencia explicable porque las pacientes tenían síntomas de infección del tracto urinario.…”
Section: Discussionunclassified